2008
DOI: 10.1598/rrq.43.4.3
|View full text |Cite
|
Sign up to set email alerts
|

“The Blues Playingest Dog You Ever Heard Of”: (Re)positioning Literacy Through African American Blues Rhetoric

Abstract: Building on scholarship in African American rhetorics and African American language, an analysis of Walter Dean Myers's (2000) The Blues of Flats Brown is presented as a methodology for (re)imagining educational issues and research related to voice, agency, reading, and literacy in the face of racial oppression and subjugation. In the analysis, blues music is viewed as an articulation of the reciprocal relationship between the political, economic, historical, and social struggles of African American masses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Based on this body of scholarship and similar intellectual propositions (cf., Kynard, 2008;West, 2008;Wible, 2006), adjectives such as "disengaged" when applied to youth readers and writers are not only inaccurate, they are misplaced. Youths are not failing to engage texts; many of the texts we teach Youths are not failing to engage texts; many of the texts we teach in schools are failing to engage youth.…”
Section: Literacy Engagementmentioning
confidence: 99%
“…Based on this body of scholarship and similar intellectual propositions (cf., Kynard, 2008;West, 2008;Wible, 2006), adjectives such as "disengaged" when applied to youth readers and writers are not only inaccurate, they are misplaced. Youths are not failing to engage texts; many of the texts we teach Youths are not failing to engage texts; many of the texts we teach in schools are failing to engage youth.…”
Section: Literacy Engagementmentioning
confidence: 99%
“…Perdomo encourages children to love the art of writing, gives them a positive attitude toward themselves and gives them knowledge of black heritage and a particular black icon. Just as Margaret responded to the rhythm in Perdomo's prose, many black children will recognize tonal and rhythmic qualities similar to the black rhetoric found in their homes (Kynard, 2008). Wendy's initial reaction to this story had more to do with style and comfort level than with the content or literary quality of the book.…”
Section: Discussionmentioning
confidence: 99%
“…We focused only on the phonological and grammatical features of AAL. Kynard (2008) observed that theorists have researched discourse strategies used by African American rhetorics, such as call-response and field-dependent strategies: signifying, tonal semantics, and directness. These strategies were vitally important in understanding the semantics and pragmatics of AAL.…”
Section: The Authors' Positionalitymentioning
confidence: 99%